Simple Data Sharing for Multi-Tasked Goal-Oriented Problems - Fan, Ying; Li, Jingling; Swaminathan, Adith; Modi, Aditya; Cheng, Ching-An (NeurIPS 2023, 2023)
Many important sequential decision problems – from robotics, games to logistics – are multi-tasked and goal-oriented. In this work, we frame them as Contextual Goal Oriented (CGO) problems, a goal-reaching special case of the contextual Markov decision process. CGO is a framework for designing multi-task agents that can follow instructions (represented by contexts) to solve goal-oriented tasks. We show that CGO problem can be systematically tackled using datasets that are commonly obtainable: an unsupervised interaction dataset of transitions and a supervised dataset of context-goal pairs. Leveraging the goal-oriented structure of CGO, we propose a simple data sharing technique that can provably solve CGO problems offline under natural assumptions on the datasets' quality. While an offline CGO problem is a special case of offline reinforcement learning (RL) with unlabelled data, running a generic offline RL algorithm here can be overly conservative since the goal-oriented structure of CGO is ignored. In contrast, our approach carefully constructs an augmented Markov Decision Process (MDP) to avoid introducing unnecessary pessimistic bias. In the experiments, we demonstrate our algorithm can learn near-optimal context-conditioned policies in simulated CGO problems, outperforming offline RL baselines.